2007
DOI: 10.1038/sj.leu.2404589
|View full text |Cite|
|
Sign up to set email alerts
|

A sub-population of high proliferative potential-quiescent human mesenchymal stem cells is under the reversible control of interferon α/β

Abstract: Type I interferon (IFN) is shown to control the reversible quiescence of a primitive human bone marrow mesenchymal stem cell (MSC) subpopulation. A 24 h pre-treatment of Stro1 þ / GlycoA-or CD45-/GlycoA-subpopulations with a monoclonal antibody (mAb) against the IFNAR1 chain of the human type I IFN receptor (64G12), or with a polyclonal anti-IFNa antibody, resulted in a marked increase in the number of very large colonies (CFU-F 43000 cells) obtained in the presence of low, but necessary, concentrations of bFG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…The presence of subpopulations is not a new finding regarding MSCs, as this has been widely reported for BM‐MSCs (Nasef et al , 2009; Hatzfeld et al , 2007; Liu et al , 2006). However, to our knowledge, the present study reports for the first time results demonstrating that adipose stem cells are composed of subpopulations.…”
Section: Discussionmentioning
confidence: 89%
“…The presence of subpopulations is not a new finding regarding MSCs, as this has been widely reported for BM‐MSCs (Nasef et al , 2009; Hatzfeld et al , 2007; Liu et al , 2006). However, to our knowledge, the present study reports for the first time results demonstrating that adipose stem cells are composed of subpopulations.…”
Section: Discussionmentioning
confidence: 89%
“…MSCs are highly heterogeneous and differ in their surface marker composition, shape and capacity for proliferation and differentiation [44]. It is possible that only a subset of MSCs within a population possesses multipotent differentiation potential and promotes tumorigenesis, while another subset inhibits tumorigenesis.…”
Section: Phenotypically and Functionally Heterogeneous Mscsmentioning
confidence: 99%
“…In a previous study [8], we observed that a 24 h pretreatment of Stro1+/GlycoA− or CD45−/GlycoA− hMSCs with a monoclonal antibody blocking the human type I interferon-alpha (IFN α ) receptor, or with a polyclonal anti-IFN α antibody, resulted in a marked increase in the number of very large colonies (Colony-forming Units-fibroblasts containing more than 3000 cells). Interestingly, these activated High Proliferative Potential-Quiescent hMSCs (HPP-Q hMSCs) expressed SSEA-3 and -4 at a higher level than non-pretreated cells, suggesting that HPP-Q hMSCs constituted a more primitive cell population than nontreated cells.…”
Section: Introductionmentioning
confidence: 99%